Cavity Optomechanics with High Stress Silicon Nitride Films - Wilson, Dalziel Joseph (California Institute of Technology, 2012)
There has been a barrage of interest in recent years to marry the fields of nanomechanics and quantum optics. Mechanical systems provide sensitive and scalable architectures for sensing applications ranging from atomic force microscopy to gravity wave interferometry. Optical resonators driven by low noise lasers provide a quiet and well-understood means to read-out and manipulate mechanical motion, by way of the radiation pressure force. Taken to an extreme, a device consisting of a high-Q nanomechanical oscillator coupled to a high-finesse optical cavity may enable ground-state preparation of the mechanical element, thus paving the way for a new class of quantum technology based on chip-scale phononic devices coupled to optical photons. By way of mutual coupling to the optical field, this architecture may enable coupling of single phonons to real or artificial atoms, an enticing prospect because of the vast "quantum optics toolbox" already developed for cavity quantum electrodynamics.

The first step towards these goals --- ground-state cooling of the mechanical element in a "cavity optomechanical" system --- has very recently been realized in a cryogenic setup. The work presented in this thesis describes an effort to extend this capability to a room temperature apparatus, so that the usual panoply of table-top optical/atomic physics tools can be brought to bear. This requires a mechanical oscillator with exceptionally low dissipation, as well as careful attention to extraneous sources of noise in both the optical and mechanical componentry. Our particular system is based on a high-Q, high-stress silicon nitride membrane coupled to a high-finesse Fabry-Perot cavity. The purpose of this thesis is to record in detail the procedure for characterizing/modeling the physical properties of the membrane resonator, the optical cavity, and their mutual interaction, as well as extraneous sources of noise related to multimode thermal motion of the oscillator, thermal motion of the cavity apparatus, optical absorption, and laser phase fluctuations. Our principle experimental result is the radiation pressure-based cooling of a high order, 4.8 MHz drum mode of the membrane from room temperature to ~ 100 mK (~ 500 phonons). Secondary results include an investigation of the Q-factor of membrane oscillators with various geometries, some of which exhibit state-of-the-art Q x frequency products of 3 x 10^13 Hz, and a novel technique to suppress extraneous radiation pressure noise using electro-optic feedback.
Keywords: Physics; Optomechanics Silicon Nitride Membrane